2010 IEEE International Conference on Integrated Circuit Design and Technology 2010
DOI: 10.1109/icicdt.2010.5510283
|View full text |Cite
|
Sign up to set email alerts
|

3D integration: Advantages, enabling technologies & applications

Abstract: The microelectronic industry has arrived at a crossroads. There is the challenge of continued Moore's Law scaling and the ever-growing consumer demand for smaller, faster electronics with extended and new functionalities. 3D integration is a promising and fastgrowing field that addresses the convergence of Moore's Law and more than Moore. 3D integration offers a path for higher performance, higher density, higher functionality, smaller form factor, and potential cost reduction. Through this emerging field, new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Its main purpose is to establish electrical connectivity between devices in two different dies in a 3D-IC stack. There is presently no consensus on the most efficient bonding technique which largely depends on the application requirements [30,32,33]. There are various bonding techniques [34] which range from direct oxide bonding, metal to metal (Cu-Cu) bonding, with different variants and adhesives.…”
Section: Vertical Interconnect Technology Development (Tsv)mentioning
confidence: 99%
“…Its main purpose is to establish electrical connectivity between devices in two different dies in a 3D-IC stack. There is presently no consensus on the most efficient bonding technique which largely depends on the application requirements [30,32,33]. There are various bonding techniques [34] which range from direct oxide bonding, metal to metal (Cu-Cu) bonding, with different variants and adhesives.…”
Section: Vertical Interconnect Technology Development (Tsv)mentioning
confidence: 99%
“…While significant R and D efforts have been expended on various planar approaches, 3DIC integration technologies are undoubtedly gaining momentum as potential pioneers in the challenge to meet the demands of the form factor, performance, and cost through this decade and beyond [3,11]. This study conducted expert interviews after reviewing the relevant literature to identify the four alternative 3DIC integration technologies-3DIC packaging, 3DIC through-silicon via (3DIC TSV), 3D silicon TSV (3D Si TSV), and 2.5D through-silicon interposer (2.5D TSI)-that are mostly the concern of the Taiwanese semiconductor industry.…”
Section: Perspectives On 3dic Integration Technologiesmentioning
confidence: 99%
“…The 3DIC packaging technologies exploit a z-axis dimension to provide a volumetric packaging solution for higher integration and performance, as well as to save space by stacking either separate chips or separate packages in a single package [11]. The two types of 3DIC packaging technologies are coined as "die stacking" or "package stacking" technologies [12].…”
Section: Dic Packagingmentioning
confidence: 99%
“…It is important to note that 3D stacking generally encompasses both silicon level stacking and packaging level stacking. Reviews of the various types of 3D stacking, and their advantages, may be found in recent publications [4][5][6][7][8][9].…”
Section: Current Statusmentioning
confidence: 99%